IMPLEMENTASI PEMBIAYAAN AKAD MURABAHAH PADA PRODUK KREDIT PEMILIKAN RUMAH (KPR) DI PT BANK SYARIAH MANDIRI KANTOR CABANG SAMBAS - Misbun (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2023)
This research uses a qualitative approach because the research is carried out in natural conditions. In addition, qualitative research is research that produces descriptive data in the form of written or oral data. While the method used in this study is descriptive research. The results of this study Home Ownership Credit Financing at BSM KC Sambas is based on the principle of buying and selling murābaḥah with a murābaḥah bil wakalah contract if the prospective customer chooses his own house to be submitted for mortgage financing, because the customer represents BSM KC Sambas to buy the house of his choice, Therefore, the Wakalah contract must be executed first and then the Murābaḥah contract can be executed. However, if the customer wants BSM KC Sambas to find a house, the Murābaḥah contract can be carried out immediately. In determining the profit margin received by BSM KC Sambas, it is carried out on the basis of deliberation and agreement between BSM KC Sambas and customers and among them accept and know each other.